2017
DOI: 10.1016/j.jfoodeng.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion of pectin- and mango-enriched diets using a dynamic rat stomach-duodenum model

Abstract: In this study we investigated the in vitro digestive behaviors of starch-based diets enriched with soluble fiber (pectin) and fruit powder (mango) varying with dry matter contents using a dynamic rat stomach and duodenum model. The changes in pH with respect to digestion time, gastric emptying, starch and protein hydrolysis as well as rheological and microstructural properties of the gastric and duodenal digesta were investigated. The effects of porcine gastric mucin on digestion were studied as well. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 46 publications
(58 reference statements)
2
31
0
Order By: Relevance
“…In this case, it is a good entry point for getting involved in the bio‐inspired chemical engineering, working on the understanding of the physiology of animal and human digestion. We have constructed uniquely the near‐real in vitro stomach systems for rats and humans . An interesting intestinal bench‐scale silicone tubular reactor was constructed and investigated for residence time distribution and, most recently, a process for hydrolysis of the very viscous solution of starch was demonstrated with the intestinal reactor .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it is a good entry point for getting involved in the bio‐inspired chemical engineering, working on the understanding of the physiology of animal and human digestion. We have constructed uniquely the near‐real in vitro stomach systems for rats and humans . An interesting intestinal bench‐scale silicone tubular reactor was constructed and investigated for residence time distribution and, most recently, a process for hydrolysis of the very viscous solution of starch was demonstrated with the intestinal reactor .…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that the DIVRSD model captures the main mechanical and biochemical events occurring in the rat stomach and duodenum (Wu et al 2017;Wu et al 2014). The rate and extent of food digestion in the DIVRSD model was found to be statistically similar to that found for rats in vivo (Wu et al 2014).…”
Section: Introductionsupporting
confidence: 56%
“…However, these models do not consider the different mixing patterns, dynamic fluid behaviour or mechanical forces encountered by food chyme when it is passed through the gastro-intestinal tract (Kong & Singh 2010). These limitations are addressed by dynamic models, which simulate physico-chemical and physiological conditions as well as representing the geometrical and morphological details of real GI tracts (Chen, Jayemanne & Chen 2013;Moreno 2007;Wu et al 2017). Some of the successful dynamic food digestion models are TNO's gastrointestinal model (TIM) (Blanquet et al 2004 in vivo studies and could be successfully used to study the integrity of food under simulated physiological and mechanical conditions (Wu et al 2017).…”
Section: In Vitro Food Digestion Modelsmentioning
confidence: 99%
See 2 more Smart Citations